Performance of HPV testing, Pap smear and VIA in women attending cervical cancer screening in Kilimanjaro region, Northern Tanzania: a cross-sectional study nested in a cohort. Issue 10 (31st October 2022) - Mremi, Alex; Mchome, Bariki; Mlay, Joseph; Schledermann, Doris; Blaakær, Jan; Rasch, Vibeke
Abstract : Objective: There is a concern about performance of the screening approaches, where information on the quality of novel and affordable screening approaches that will perform well in remote areas is warranted. This lack of information makes it difficult to prioritise resource use in efforts to improve cervical cancer outcomes. We aimed to compare the diagnostic value of human papillomavirus (HPV) testing on self-collected samples, Pap smear and visual inspection of the cervix with acetic acid (VIA) tests for detection of high-grade cervical intraepithelial neoplasia or worse (CIN2+). Design: A combined cross-sectional and cohort study. Setting: Three primary healthcare centres in Kilimanjaro region, Tanzania. Participants: 1620 women undergoing cervical cancer screening from December 2018 to September 2021. Inclusion criteria were being aged 25–60 years, and no history of premalignant or cervical cancer. Exclusion criteria were overt signs of cancer and previous hysterectomy. Interventions: Participants underwent HPV self-sampling with Evalyn Brush and Care HPV kit assay was used to determine prevalence of high-risk HPV infection. Women with positive HPV test were together with a random sample of HPV negative women scheduled for follow-up where VIA was performed, and Pap smear and cervical biopsies obtained. Results: Of 1620 women enrolled, 229 (14.1%) were HPV positive and 222 of these attended follow-up together with 290 (20.8%) women with negative HPV test. On VIA, 17.6% were positive. On Pap smear, 8.0% were classified as high-grade squamous intraepithelial lesion. The sensitivity and specificity, respectively, of the various tests, compared with histopathology for the detection of CIN2+ were: HPV test 62.5%, 59.3%; Pap smear 82.8%, 82.1% and; VIA 48.4%, 56.8%. When combined, the sensitivity and specificity for HPV and Pap smear were 90.6%, 70.6% while HPV and VIA were 65.6% and 75.5% for the detection of CIN2+. Conclusions: The performance of care HPV testing on self-collected samples opens the possibility of increasing coverage and early detection in resource-constrained settings.